Body image perceptions in Western and post-communist countries: a cross-cultural pilot study of children and parents - Humenikova, Lenka; Gates, Gail E (Maternal & child nutrition, 2008)
The development of an unrealistic ideal body image and body size dissatisfaction among children is common in Western countries, including the USA and many European nations. However, little is known about children's body image perceptions in post-communist countries. This pilot study evaluated body image perceptions in a sample of Czech school-aged children and their parents and compared them with the perceptions of American children and parents. Ninety-seven Czech and 45 American 4th-6th graders and their parents from eight urban schools participated in this study. A previously developed silhouette body image instrument was utilized in a parent questionnaire and during child interviews to measure perceived and ideal body image perceptions of children and parents. Descriptive statistics, independent t-tests and paired t-tests were used to compare differences between children's and parents' perceived and ideal body image perceptions. Associations between body image perceptions and other variables were explored using bivariate correlations. American children had a thinner ideal body image compared with Czech children (P < 0.05). However, a larger proportion of Czech boys desired to be thinner compared with American boys (34.2% vs. 20%). Parent's ideal body image for their children did not differ by nationality (P = 0.858). While the pressure on children to look thinner was apparent among both American and Czech children, Czech children considered a larger body size as more ideal. A future study should evaluate body image perceptions and factors influencing these perceptions in a representative sample of Czech children and parents.
Keywords: dětská psychologie; Cross-Cultural Comparison; Male; Overweight; Self Concept; Obesity; Parents; hubenost; Česká republika; Child; pilotní projekty; sebepojetí; dítě; obezita; Adult; dospělí; mužské pohlaví; nadváha; představa o vlastním těle; Czech Republic; Psychology, Child; Thinness; rodiče; lidé; United States; ženské pohlaví; Body Size; Humans; Body Mass Index; velikost těla; index tělesné hmotnosti; Spojené státy americké; Body Image; Pilot Projects; Female; srovnání kultur